Trabalho pedagógico dos professores de educação infantil de Santa Maria/RS: uma análise dos movimentos de sentidos nos projetos pedagógicos escolares - Dutra, Larissa dos Santos (2022)
This dissertation is part of the Postgraduate Program in Education (PPGE) at the Federal University of Santa Maria (UFSM), in Research Line 2 - Public Educational Policies, Educational Practices and their Interfaces, and in the studies developed in Kairós - Study and Research Group on Work, Education and Educational Policies. It presents a study that aimed to analyze the movements of senses evidenced in the pedagogical projects of Municipal Schools of Early Childhood Education (EMEI's) of Santa Maria/RS about the pedagogical work (TP) of teachers. The research proposal and the general objective defined emerged from the work developed in Early Childhood Education (ECE), and from the senses constructed by it. It was observed, in this process, the need to define and affirm the work of teachers with children in daycare and preschools in a documental scope, since the effectiveness of the pedagogical work at this level of Basic Education is regulated by Public Policies developed locally and nationally. The study was organized based on theoretical references about the history of Brazilian children's education throughout the 20th century and, as a result of this trajectory, the contributions of the past to the current school care. There was also an analysis of Public Educational Policies for Early Childhood Education and a search for scientific productions with the categories of analysis being pedagogical work, teaching work, and teachers' work in Early Childhood Education. Subsequently, the municipal establishments of Early Childhood Education were quantified, and contact was established with the EMEI's of Santa Maria in order to produce data through the documental analysis of the school pedagogical projects, considering the evidence of the TP in these documents. The theoretical and methodological basis of the research was the Analysis of the Movements of Senses (AMS), which made it possible to perceive approximations and divergences in the senses produced during the study. It was found that the pedagogical work, in these realities, is constituted by senses coming from other relations, such as valorization of the work inside the school, specificities of the work with young children (interaction, knowledge of oneself and of the other, education and care, language) and standardization by means of the Public Policies elaborated for this context.